2006
DOI: 10.1097/01.aids.0000226959.87471.01
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death in adults receiving highly active antiretroviral therapy in Senegal: a 7-year cohort study

Abstract: This study underlines the early mortality pattern after HAART initiation and highlights the leading role of mycobacterial infections in the causes of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
199
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(252 citation statements)
references
References 27 publications
44
199
5
Order By: Relevance
“…This higher mortality rate was similar with studies conducted in different Africa countries [5,7,[9][10][11][12][13]. The early deaths may reflect the late initiation of ART with the advanced clinical stage and severely compromised status of CD4 cell counts (<50 cells/ µl).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This higher mortality rate was similar with studies conducted in different Africa countries [5,7,[9][10][11][12][13]. The early deaths may reflect the late initiation of ART with the advanced clinical stage and severely compromised status of CD4 cell counts (<50 cells/ µl).…”
Section: Discussionsupporting
confidence: 87%
“…This finding is supported by other studies [5,7,10,12,14]. Consequently, it is unquestionable that ART should be started (initiated) as early as possible, prior to advanced clinical stages.…”
Section: Discussionsupporting
confidence: 79%
“…Early in the roll-out of life-saving ART, incidence rates of early mortality after ART in SSA ranged from 9% to 39% 2 and were significantly higher than in developed countries. 3 Risk factors for early mortality include low CD4 T-cell count (< 50 cells/μL) 4,5 with a combined hazard ratio (HR) across studies of 2.5 (95% confidence interval [CI]: 1.9-3.2). 4 Low body mass index (BMI < 18 kg/m 2 ) has also been associated with early mortality.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the relatively high role of homosexuality and the use of injectable drugs in the North in the transmission of the disease. In Senegal, Etard et al [17], found a sample of 404 patients on ARV with an average age of 37 years ± 6. Studies on the ARs of ARVs performed in Mali [14], Cotonou [18] and Iran [19] noted an average age of 35 years, 41 years and 36 years, respectively, with a female predominance.…”
Section: Discussionmentioning
confidence: 99%